L'entrée en enseignement professionnel au Québec : un long parcours de transition en tension entre le métier exercé et le métier enseigné - André Balleux (Nantes Université, 2011)
In this research project we followed vocational training teachers in Quebec during their entry into the teaching profession. Three salient features mark the beginning of their career: transition from practicing their occupation to the teaching profession, immersion into teaching, and integration into a vocational training center at the same time as into a university teacher education program. After four years of research on the first aspect, the transition from their occupation to teaching, the process appeared as a segment of professional life divided into four major periods: the time of practicing their occupation, the time of change, the time of entry into teaching, and the time of professional consolidation. But beyond these four steps, we observe the meeting of two dimensions of time: the biographical trajectory which makes sense of the transition at a particular time in life, and the daily process in which the person is grappling with several changes which affect them. At the end of this journey, if the passage into the teaching profession is successful, a renewed vocational maturity emerges.